The influence of sex, gender, age, and ethnicity on psychosocial factors and substance use throughout phases of the COVID-19 pandemic. - Lori A Brotto (Public Library of Science (PLoS), 2021)
Objectives The SARS-CoV-2 (COVID-19) pandemic has had profound physical and mental health effects on populations around the world. Limited empirical research has used a gender-based lens to evaluate the mental health impacts of the pandemic, overlooking the impact of public health measures on marginalized groups, such as women, and the gender diverse community. This study used a gender-based analysis to determine the prevalence of psychosocial symptoms and substance use (alcohol and cannabis use in particular) by age, ethnicity, income, rurality, education level, Indigenous status, and sexual orientation. Methods Participants in the study were recruited from previously established cohorts as a part of the COVID-19 Rapid Evidence Study of a Provincial Population-Based Cohort for Gender and Sex (RESPPONSE) study. Those who agreed to participate were asked to self-report symptoms of depression, anxiety, pandemic stress, loneliness, alcohol use, and cannabis use across five phases of the pandemic as well as retrospectively before the pandemic. Results For all psychosocial outcomes, there was a significant effect of time with all five phases of the pandemic being associated with more symptoms of depression, anxiety, stress, and loneliness relative to pre-COVID levels (p < .0001). Gender was significantly associated with all outcomes (p < .0001) with men exhibiting lower scores (i.e., fewer symptoms) than women and gender diverse participants, and women exhibiting lower scores than the gender diverse group. Other significant predictors were age (younger populations experiencing more symptoms, p < .0001), ethnicity (Chinese/Taiwanese individuals experiencing fewer symptoms, p = .005), and Indigenous status (Indigenous individuals experiencing more symptoms, p < .0001). Alcohol use and cannabis use increased relative to pre-pandemic levels, and women reported a greater increase in cannabis use than men (p < .0001). Conclusions Our findings highlight the need for policy makers and leaders to prioritize women, gender-diverse individuals, and young people when tailoring public health measures for future pandemics.